A review of the effects of Helicobacter pylori infection on reproduction, pregnancy and gynecologic diseases - Elham Kazemi; Mozafar Khazaei (Mashhad University of Medical Sciences, 2018)
Introduction: Helicobacter pylori (Hp) infections, in addition to stomach disorders, are associated with colonization in the genital tract, causing some gynecologic problems, infertility and abortion. The prevalence of this contamination is about 50% in the world and is higher in third world countries. Recent studies have proposed the association between the infection with this bacterium and the gynecologic diseases, pregnancy problems, ovarian cysts, polycystic ovarian syndrome (PCOS / PCOS), abortion and even male infertility. This review article was performed with aim to evaluate the effect of Hp infection on pregnancy and gynecologic diseases. Methods: This review article was performed by searching the key words including Helicobacter pylori, H. pylori, abortion, breast cancer, PCOS, hyperemesis gravidarum, anemia and pregnancy, and their possible combination using the databases of Scopus, Pubmed, Web of Science, Iran medex and SID since 2001 to 2017. Then all Persian and English articles which had the inclusion criteria were evaluated. Results: 31 articles were eligible for inclusion in the study. In most of these studies, the significant relationship was found between Hp and infertility (P<0.05); but there was contradiction with some variables such as ovarian cyst and abortion. There was also no significant relationship between Hp and breast cancer and ectopic pregnancy. Some studies have suggested the role of Hp in iron deficiency anemia and hyperemesis gravidarum. Conclusion: Considering the role of Hp in the etiology of infertility, abortion, PCOS, anemia and hyperemesis gravidarum, it is recommended that serologic Hp tests be performed before starting treatment in all these cases.